The association of end-spurt behaviour with seasonal best time in long-distance freestyle pool swimming - Neuloh, J. E.; Venhorst, A.; Forster, S.; Mauger, A. R.; Meyer, T. (European Journal of Sport Science, 2023)
To analyse the association of seasonal best time, distance and different performance levels with end-spurt behaviour in one swimming season. Race results in 800 and 1500 m pool freestyle swimming in the season 2018/2019 including 14,930 races and 2650 swimmers were obtained. The end-spurt for each race was determined by means of an End-Spurt Indicator (ESI). Subsequently, ESI was used as a dependent variable and influences were analysed using a linear mixed model with fixed effects for seasonal best time, distance, and performance level amongst others. In the 800 and 1500 m races swimmers showed a mean ESI of 2.08 (95% CI: 2.02-2.13) and 3.68 (95% CI: 3.59-3.76), respectively. There was a significant association between seasonal best time and ESI, with a better seasonal best time showing a greater ESI (F = 70.5, P < .001, f2 = 0.04). A significant effect on greater ESI was also observed for longer distance (F = 1067.5, P < .001, f2 = 0.06) and higher performance level (F = 91.1, P < .001, f2 = 0.02). Elite swimmers had a mean ESI of 5.47 (95% CI: 4.91-6.03), sub-elite swimmers of 3.74 (95% CI: 3.53-3.95) and competitive swimmers of 2.41 (95% CI: 2.37-2.46). A more pronounced end-spurt is associated with seasonal best time in long-distance pool swimming, higher performance level of the swimmer and longer race distance.